FACTORS CONTRIBUTING TO INCREASED USE OF TOBACCO AMONG THE YOUTH AGED 15-35 YEARS, IN KATWE VILLAGE, KAMPALA DISTRICT. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Kasse , John; Atukuuma, Cliffe (Student’s Journal of Health Research Africa, 2023)
Purpose of the study: The purpose of the study is to assess the factors contributing to the increased use of tobacco among the youth aged 15-35 years in Katwe village, Makindye division Objectives of the study: The specific objectives of the study were; to assess the individual factors contributing to the increased use of tobacco among the youth aged 15-35 years in Katwe Villega, to identify the economic factors contributing to the increased use of tobacco among the youth aged 15-35 years and to find out the community factors contributing to the increased use of tobacco among the youth aged 15-35 years in Katwe village, Makindye village. Methodology: The study design employed was the descriptive cross-sectional study to address the specific objectives of the study on the sample of 50 respondents using a simple random sampling technique. Some structured questionnaires were designed and used as the data collection tool. Results of the study: The majority of the respondents 80% do smoke tobacco 62% smoke smokeless tobacco and 54% got the information from friends, 60% said their parents influenced them to smoke, 82% of the respondents are salary earners 70 % are influenced by the salary to smoke. Conclusion: In conclusion, the overall results on the individual factors, community factors, and economic factors contributed to the increased use of tobacco among the youth aged 15-35 years. Recommendation: The Ministry of Health should increase taxes on tobacco sales to reduce tobacco use by the youth Secondly, it should be imperative that all stakeholders engage in concerted efforts to target both schools and out-of-school youths in tobacco control strategies Also, effective smoking prevention programs should take into account the dominant influences of peer groups in the onset and continuation of smoking.